Docetaxel chemotherapy response in PC3 prostate cancer mouse model detected by rotating frame relaxations and water diffusion - Laakso Hanne; Ylä-Herttuala Elias; Sierra Alejandra; Jambor Ivan; Poutanen Matti; Liljenbäck Heidi; Virtanen Helena; Merisaari Harri; Aronen Hannu; Minn Heikki; Roivainen Anne; Liimatainen Timo (WILEY, 2022)
MRI is a common method of prostate cancer diagnosis. Several MRI-derived markers, including the apparent diffusion coefficient (ADC) based on diffusion-weighted imaging, have been shown to provide values for prostate cancer detection and characterization. The hypothesis of the study was that docetaxel chemotherapy response could be picked up earlier with rotating frame relaxation times TRAFF2 and TRAFF4 than with the continuous wave T1ρ, adiabatic T1ρ, adiabatic T2ρ, T1, T2 or water ADC. Human PC3 prostate cancer cells expressing a red fluorescent protein were implanted in 21 male mice. Docetaxel chemotherapy was given once a week starting 1 week after cell implantation for 10 randomly selected mice, while the rest served as a control group (n = 11). The MRI consisted of relaxation along a fictitious field (RAFF) in the second (RAFF2) and fourth (RAFF4) rotating frames, T1 and T2, continuous wave T1ρ, adiabatic T1ρ and adiabatic T2ρ relaxation time measurements and water ADC. MRI was conducted at 7 T, once a week up to 4 weeks from cell implantation. The tumor volume was monitored using T2-weighted MRI and optical imaging. The histology was evaluated after the last imaging time point. Significantly reduced RAFFn, T1ρ,T2ρ and conventional relaxation times 4 weeks after tumor implantation were observed in the treated tumors compared with the controls. The clearest short- and long-term responses were obtained with T1, while no clear improvement in response to treatment was detected with novel methods compared with conventional methods or with RAFFn compared with all others. The tumor volume decreased after a two-week time point for the treated group and increased significantly in the control group, which was supported by increasing red fluorescent light emission in the control tumors. Decreased relaxation times were associated with successful chemotherapy outcomes. The results indicate altered relaxation mechanisms compared with higher dose chemotherapies previously published.